2019
DOI: 10.1002/mrm.27663
|View full text |Cite|
|
Sign up to set email alerts
|

Improved chemical exchange saturation transfer imaging with real‐time frequency drift correction

Abstract: Purpose To investigate the effects of frequency drift on chemical exchange saturation transfer (CEST) imaging at 3T, and to propose a new sequence for correcting artifacts attributed to B0 drift in real time. Theory and Methods A frequency‐stabilized CEST (FS‐CEST) imaging sequence was proposed by adding a frequency stabilization module to the conventional non‐frequency‐stabilized CEST (NFS‐CEST) sequence, which consisted of a small tip angle radiofrequency excitation pulse and readout of three non‐phase‐encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 37 publications
0
45
0
Order By: Relevance
“…Thus, the required time is approximately the same as for conventional 1 H‐MRSI, which has already been demonstrated to be applicable in a clinical routine. To further improve the current acquisition protocol, a real‐time frequency drift correction as recently proposed for the MTR asym analysis could be included, although it was not required in this work because the small changes in B 0 at 3 T of about 0.02 ppm during a 20‐minute examination are compensated for by the Lorentzian fitting. For the next step, this acquisition protocol will be used to comprehensively assess the actual clinical relevance of relaxation compensation in CEST‐MRI for various neuro‐oncological clinical questions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the required time is approximately the same as for conventional 1 H‐MRSI, which has already been demonstrated to be applicable in a clinical routine. To further improve the current acquisition protocol, a real‐time frequency drift correction as recently proposed for the MTR asym analysis could be included, although it was not required in this work because the small changes in B 0 at 3 T of about 0.02 ppm during a 20‐minute examination are compensated for by the Lorentzian fitting. For the next step, this acquisition protocol will be used to comprehensively assess the actual clinical relevance of relaxation compensation in CEST‐MRI for various neuro‐oncological clinical questions.…”
Section: Discussionmentioning
confidence: 99%
“…CEST studies so far have been performed mostly with 2D acquisitions or 3D acquisitions with a limited spatial coverage, likely due to the technical difficulty of achieving high spatial coverage, short acquisition, and few artifacts simultaneously. Although 3D acquisition with a limited spatial coverage can suffice in many situations, CEST imaging with whole‐brain coverage may be needed in cases in which multiple lesions exist in the brain or in cases when conventional anatomical images do not reveal clear locations of pathology .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, because the experiments were carried out on a research‐dedicated scanner, no significant frequency drift was encountered in this study. However, the real‐time frequency stabilization module should be incorporated into the SPACE‐CEST sequence in future work when the sequence is deployed on intensively used clinical scanners.…”
Section: Discussionmentioning
confidence: 99%
“…The original GRE FS-CEST sequence inserted a GRE frequency stabilization module in front of the conventional NFS-CEST sequence that was composed of three modules including CEST saturation, fat suppression (eg, spectral presaturation with inversion recovery [SPIR]), and readout (eg, turbo spin echo [TSE]). 28 In this study, the schematic diagram of the proposed FID FS-CEST sequence is shown in Figure 1, K E Y W O R D S chemical exchange saturation transfer (CEST), free-induction-decay (FID) readout, frequency stabilization, temporal B 0 drift in which the FID frequency stabilization module replaces the previous GRE one while retaining the succeeding CEST saturation, SPIR fat suppression, and TSE readout modules. For the proposed FID FS-CEST sequence, the frequency stabilization module commences with a small-flip-angle sinc excitation pulse in conjunction with a slice-selective gradient, followed by a single k-space line of FID readout and spoiler gradients at the end of the module.…”
Section: Proposed Sequencementioning
confidence: 99%
“…To correct the B 0 drift in CEST imaging prospectively, we recently proposed a frequency-stabilized CEST (FS-CEST) sequence by inserting a frequency stabilization module, in which three k-space lines of GRE readout were acquired, in front of the conventional non-frequency-stabilized CEST (NFS-CEST) sequence. 28 In this study, the frequency stabilization module of the FS-CEST sequence was simplified by replacing the original three k-space lines of gradient-echo (GRE) readout with a single k-space line of free-induction-decay (FID) readout. The proposed method reduced the complexity of the sequence design, shortened the minimal readout time, and allowed a greater phase-wrap-free frequency to be corrected.…”
Section: Introductionmentioning
confidence: 99%